Obtención de microesferas a partir de acrilamida por el método de polimerización en suspensión inversa (2010)
The microspheres possess major superficial area that the same quantity of polymerized monomer in mass, which offers advantages of interaction with the medium, as much to absorb water as for other purposes. His obtain depends on a series of specific conditions that, if not being apropiated, cannot react adequately and will precipitate in mass. By means of the use of acrilamide monomer, the crosslinker Nmetilenbisacrilamide, the initiator agent ammonium persulfate, water as a dissolution agent and toluene as the continuous phase; all of them mixed and shaken in the process of polymerization in inverse suspension, were prepared hidrogels in individual microspheres shape.